2015
DOI: 10.1002/syn.21833
|View full text |Cite
|
Sign up to set email alerts
|

G‐protein‐coupled inward rectifier potassium channels involved in corticostriatal presynaptic modulation

Abstract: Presynaptic modulation has been associated mainly with calcium channels but recent data suggests that inward rectifier potassium channels (K(IR)) also play a role. In this work we set to characterize the role of presynaptic K(IR) channels in corticostriatal synaptic transmission. We elicited synaptic potentials in striatum by stimulating cortical areas and then determined the synaptic responses of corticostriatal synapsis by using paired pulse ratio (PPR) in the presence and absence of several potassium channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…G bg subunits bind and activate G proteingated inwardly rectifying K 1 channels (GIRK) (Bünemann et al, 2001) and transfected hH 3 R 445 and hH 3 R 365 activate channels formed by the GIRK1 (Kir3.1) and GIRK4 (Kir3.4) subunits expressed in Xenopus oocytes (Sahlholm et al, 2012). GIRKs can inhibit synaptic transmission (Meneses et al, 2015), and activation of presynaptic GIRKs would thus represent an additional mechanism for H 3 Rs to modulate neurotransmitter release. Activation of GIRK channels by H 3 Rs has also been observed at the postsynaptic level in neurons producing melanin-concentrating hormone (MCH), where the effect was prevented by GDPbS, an inhibitor of G-protein signaling (Parks et al, 2014).…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…G bg subunits bind and activate G proteingated inwardly rectifying K 1 channels (GIRK) (Bünemann et al, 2001) and transfected hH 3 R 445 and hH 3 R 365 activate channels formed by the GIRK1 (Kir3.1) and GIRK4 (Kir3.4) subunits expressed in Xenopus oocytes (Sahlholm et al, 2012). GIRKs can inhibit synaptic transmission (Meneses et al, 2015), and activation of presynaptic GIRKs would thus represent an additional mechanism for H 3 Rs to modulate neurotransmitter release. Activation of GIRK channels by H 3 Rs has also been observed at the postsynaptic level in neurons producing melanin-concentrating hormone (MCH), where the effect was prevented by GDPbS, an inhibitor of G-protein signaling (Parks et al, 2014).…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…The emerging picture of K + channels at the cortical synapse becomes richer and more complex every time. We have previously shown that glutamate release from cortical presynaptic terminals is influenced by the presence of several types of K + ‐channels, including K V 1, K V 3, and K IR 3 (Meneses et al, ). In this study, we have used BK‐specific and nonspecific K + ‐channels blockers to explore the presence and influence of presynaptic BK channels.…”
Section: Discussionmentioning
confidence: 99%
“…However, for some years now, it has become more evident that potassium channels are also present at presynaptic sites, where they contribute to fine‐tuning synaptic transmission. (Dodson & Forsythe, ; Meneses, Mateos, Islas, & Barral, , 2016; Rama, Zbili, & Debanne, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations